Becoming Neanderthals : the earlier British Middle Palaeolithic - Scott, Beccy (Oxbow Books ; The David Brown Book Company, 2011)
It is now widely accepted that by the later Middle Palaeolithic Neanderthals possessed a wide range of social and practical skills. More recently, researchers have become interested in how these skills actually emerged; in effect, the challenge now is to document the process by which Middle Pleistocene hominids "became Neanderthals". This book explores the development of classically Neanderthal behaviours in Europe between MIS 9-6, focusing on the British record, especially stone tools as durable residues of human action. As a geographically constrained study area, the progressively robust British chronometric framework now allows previously invisible patterning in technological behaviour, hominid habitat preference and demography during this period to be investigated. This book examines the immense technological variation that is apparent between British sites, in order to present a picture of changing human behaviour and the emergence of European Neanderthal adaptations.--